PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN KELARUTAN DAN HASIL KALI KELARUTAN DI KELAS XI IPA SMAN 10 PEKANBARU - Nuriah Habibah; Erviyenni Erviyenni; Susilawati Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The Research about application of the learning inquiry was conducted to improve student’s achievement on the topic of solubility and solubility product constant in class XI IPA SMAN 10 Pekanbaru. This research was experimental research based on pretest-posttest design. The samples of this research were the students of class Xl IPA 5 as the control class and students of class XI IPA 4 as the experimental class that randomly selected after testing homogeneity. Test experimental class was applied learning inquiry, while the control class was not. Applied data analysis technique used is the t-test. Based on analysis of data obtained tarithmetic> ttable is 2,27 > 1,66, means that the application of learning inquiry can improve student achievement on the subject the result solubility and solubility product constant in class XI Science SMAN 10 Pekanbaru go with the inereasing percentage of 7,09%.KeyWords : Learning inquiry, Learning Achievement . Solubility and Solubility Product Constant